Longitudinal changes in aortic distensibility in patients with Marfan syndrome. (14th October 2021) - Van Andel, M M; De Waard, V; Timmermans, J; Scholte, A J H A; Van Den Berg, M P; Zwinderman, A H; Mulder, B J M; Groenink, M
Abstract: Background: Patients with Marfan syndrome (MFS) may develop aortic dissection due to progressive dilatation in the entire aorta. Increased aortic stiffness, i.e.a. decreased distensibility has been shown to often precede these dismal sequelae. Therefore, we investigated longitudinal changes in aortic distensibility throughout the entire aorta by means of Cardiac Magnetic Resonance (CMR) imaging in patients with MFS. Methods: This retrospective study included all MFS patients with four CMR examinations performed between 1996 and 2012. Aortic distensibility was measured and calculated by a single analyst, in the ascending, proximal- and distal descending, and abdominal aorta. Changes in distensibility were studied using linear mixed-effects regression models. Furthermore, we investigated the association between distensibility and age, sex, blood pressure, medication use, FBN1 mutation type, and previous aortic root surgery. Results: In total, 35 MFS patients (age at inclusion 28 [IQR 23–32] years, 54% male) were included. Mean aortic distensibility was low in the ascending and proximal descending aorta (resp. 3.25±1.87, 3.91±1.73x10 –3 mmHg –1 ) at the first scan. Distensibility decreased significantly over time at level 2, 3, and 4 (resp. p=0.021, p=0.002, p=0.038) (Figure 1). The rate of distensibility loss per year (x10 –3 mmHg –1 /year) was respectively 0.04 and 0.06 in the proximal- and distal descending aorta. Men seemed to have a lower but more stable distensibility, whereas women showed a higher distensibility at younger age, but a faster deterioration rate over time (difference in distensibility loss per year between men and women: 0.08, p=0.038). Distensibility did not correlate significantly with medication use, FBN1 mutation type or previous aortic root surgery. Conclusion: Patients with MFS have low distensibility at all levels of the aorta at young age, which keeps decreasing over time. Men had lower distensibility at younger age than women. Distensibility was stably low in men, while still deteriorating over time in women. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): AMC FoundationHorstingstuit Foundation